CRT Survey II: a European Society of Cardiology survey of cardiac resynchronisation therapy in 11 088 patients—who is doing what to whom and how?. (19th February 2018) - Dickstein, Kenneth; Normand, Camilla; Auricchio, Angelo; Bogale, Nigussie; Cleland, John G.; Gitt, Anselm K.; Stellbrink, Christoph; Anker, Stefan D.; Filippatos, Gerasimos; Gasparini, Maurizio; Hindricks, Gerhard; Blomström Lundqvist, Carina; et al.
Abstract : Background: Cardiac resynchronisation therapy (CRT) reduces morbidity and mortality in appropriately selected patients with heart failure and is strongly recommended for such patients by guidelines. A European Society of Cardiology (ESC) CRT survey conducted in 2008–2009 showed considerable variation in guideline adherence and large individual, national and regional differences in patient selection, implantation practice and follow‐up. Accordingly, two ESC associations, the European Heart Rhythm Association and the Heart Failure Association, designed a second prospective survey to describe contemporary clinical practice regarding CRT. Methods and results: A survey of the clinical practice of CRT‐P and CRT‐D implantation was conducted from October 2015 to December 2016 in 42 ESC member countries. Implanting centres provided information about their hospital and CRT service and were asked to complete a web‐based case report form collecting information on patient characteristics, investigations, implantation procedures and complications during the index hospitalisation. The 11 088 patients enrolled represented 11% of the total number of expected implantations in participating countries during the survey period; 32% of patients were aged ≥75 years, 28% of procedures were upgrades from a permanent pacemaker or implantable cardioverter‐defibrillator and 30% were CRT‐P rather than CRT‐D. Most patients (88%) had a QRS duration ≥130 ms, 73% had left bundle branch block and 26% were in atrial fibrillation at the time of implantation. Large geographical variations in clinical practice were observed. Conclusion: CRT Survey II provides a valuable source of information on contemporary clinical practice with respect to CRT implantation in a large sample of ESC member states. The survey permits assessment of guideline adherence and demonstrates variations in patient selection, management, implantation procedure and follow‐up strategy.